2016
DOI: 10.1002/jso.24241
|View full text |Cite
|
Sign up to set email alerts
|

Rare breast cancer: 246 invasive secretory carcinomas from the National Cancer Data Base

Abstract: SBC is an uncommon tumor that is often well-differentiated and seen in younger women. Contrary to prior reports, they are frequently hormone receptor-positive. Compared to IDC, overall survival is improved. J. Surg. Oncol. 2016;113:721-725. © 2016 Wiley Periodicals, Inc.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
76
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(78 citation statements)
references
References 32 publications
1
76
1
Order By: Relevance
“…Most cases of secretory carcinoma lack or weakly express oestrogen receptor (ER) and progesterone receptor (PR). Secretory carcinoma has also been shown to lack human epidermal growth factor receptor 2 (HER2) overexpression and HER2 gene amplification . Despite this triple‐negative immunophenotype, the clinical course of secretory carcinoma is typically indolent.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…Most cases of secretory carcinoma lack or weakly express oestrogen receptor (ER) and progesterone receptor (PR). Secretory carcinoma has also been shown to lack human epidermal growth factor receptor 2 (HER2) overexpression and HER2 gene amplification . Despite this triple‐negative immunophenotype, the clinical course of secretory carcinoma is typically indolent.…”
Section: Introductionmentioning
confidence: 99%
“…These lethal cases were mainly reported in older patients; however, two cases were initially diagnosed in adolescent patients, who ultimately succumbed to their disease in their 20s. Given the paucity of cases, consensus on optimal management of secretory carcinoma has remained elusive . Although surgical excision has been curative in most patients, chemotherapy and radiation therapy have been utilised in clinically aggressive cases.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Secretory carcinoma is a rare tumor with frequency less than 0.15% of all breast cancers.Mean age in a study was found to be 25 years with female predominance [4]. However a recent study conducted on 246 invasive secretory carcinomas showed mean age of 56.4 years [5]. This goes against the previous view that it is found predominantly in children.…”
Section: Discussionmentioning
confidence: 78%